An easy method of preparing ozone gas sensors based on ZnO nanorods - Catto, Ariadne C.; Silva, Luis F. da [UNESP]; Ribeiro, Caue; Bernardini, Sandrine; Aguir, Khalifa; Longo, Elson [UNESP]; Mastelaro, Valmor. R. (Royal Soc Chemistry, 2015)
One-dimensional (1D) ZnO nanorod-like structures were successfully grown via a hydrothermal method to be used as an ozone gas sensor. X-ray diffraction measurements (XRD) and field-emission scanning electron microscopy (FE-SEM) analysis revealed a preferential growth of the nanorod-like structures along the [002] direction. Electrical resistance measurements indicated a good sensitivity to different ozone concentrations (0.06-1.19 ppm) as well as long-term stability over a 6 month period at 250 degrees C. In addition, it was observed that the nanorods had a good sensitivity to ozone at room temperature when the sensor was exposed to UV illumination. This study provides an easy and efficient way to obtain 1-D ZnO nanorods exhibiting remarkable properties for applications as ozone gas sensing materials.